ANALISIS DISLEKSIA FONOLOGIS SISWA KELAS 4 SDN KARANGBALE 04 - Anawati, Nely; Diah Sunarsih; Didik Tri Setiyoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the existence of elementary school students who experienced reading difficulties leading to phonological dyslexia. Phonological dyslexia is a reading disorder related to difficulties in recognizing, distinguishing, and connecting language sounds with letter symbols, which affects students’ reading abilities. This study aimed to analyze the characteristics of phonological dyslexia, its causal factors, and its impact on the reading abilities of fourth-grade students at SD Negeri Karangbale 04. This study employed a qualitative approach with a case study design. Data collection techniques included observation, interviews, reading tests, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing using technique and source triangulation to ensure data validity. The results showed that students experienced reading difficulties such as spelling words letter by letter, stopping in the middle of words, difficulty distinguishing similar letters, letter omission, letter reversal, and hesitation while reading. In addition, students had difficulties connecting sounds with letter symbols, causing slow and less fluent reading processes. The factors causing phonological dyslexia were influenced by internal factors such as low phonological awareness, weak memory of letters, and low concentration, as well as external factors including lack of reading practice and limited use of learning media. Phonological dyslexia also affected students’ self-confidence, learning motivation, and reading comprehension abilities. Therefore, appropriate learning strategies and special assistance are needed to improve students’ reading abilities.